Mathematical Methods in Counterterrorism 2009
DOI: 10.1007/978-3-211-09442-6_20
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Analysis of Terrorism

Abstract: Two areas that are increasingly studied in the game-theoretic literature on terrorism and counterterrorism are collective action and asymmetric information. One contribution of this chapter is a survey and extension of continuous policy models with differentiable payoff functions. In this way, policies can be characterized as strategic substitutes (e. g., proactive measures), or strategic complements (e. g., defensive measures). Mixed substitute-complement models are also introduced. We show that the efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Because governments largely resort to defensive strategies, they may be unsuccessful in effectively curbing terrorism. 5 For example, Enders and Sandler found that while the global proliferation of airport metal detectors in the early 1970s led to a significant reduction in skyjackings, the subsequent rise in the number of other hostage attacks and assassinations offset the gains associated with the airport security measures. 6 Similarly, fortifying U.S. embassies prompted a substitution into assassinations.…”
Section: Introductionmentioning
confidence: 99%
“…Because governments largely resort to defensive strategies, they may be unsuccessful in effectively curbing terrorism. 5 For example, Enders and Sandler found that while the global proliferation of airport metal detectors in the early 1970s led to a significant reduction in skyjackings, the subsequent rise in the number of other hostage attacks and assassinations offset the gains associated with the airport security measures. 6 Similarly, fortifying U.S. embassies prompted a substitution into assassinations.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of leader-follower behavior on burden sharing and total output depends on the presence of strategic substitutes or complements. Possible combinations are even richer when mixed cases are considered-seeArce and Sandler (2009).…”
mentioning
confidence: 99%
“…The challenge is to issue threats that must be sufficiently unpleasant to deter terrorists, but not so repugnant as to not be carried out; these models thus carry a credibility constraint [273]. The effects of counter-terrorism policies have been studied in two strategic cases [274]: when government intervention is defensive, and a corollary to terrorist action, and when it is a proactive substitute for it. Negative responses may arise in both cases: erosion of terrorist support, if attacks cause too much damage; backlash against the government, if its response is too strong.…”
Section: Game Theoretic Models Of Terrorismmentioning
confidence: 99%